2016
DOI: 10.1002/app.44450
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PMMA/zeolite nanofibrous membrane through electrospinning and its adsorption behavior

Abstract: The present work investigates the effect of various solution parameters and electrospinning parameters on the characteristics of electrospun nanofibrous membranes. Scanning electron microscopy was used to analyze the surface morphology of the nanofibrous membrane. Adsorption test on methyl orange was also carried out and analyzed using the UV–vis. Results showed that increasing voltage decreased mean nanofiber diameter. Meanwhile, increasing PMMA concentration, feed rate, distance between collector‐and‐needle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In this study, two concentrations of polyurethane solution, 10 and 15 wt % are used for electrospinning. Many studies have reported that electrospun fibers with lower concentration of polymer solution have smaller diameters . PU1 is the only sample electrospun from 10 wt % polyurethane solution and it has smaller average diameter than all the samples, except for PU5.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…In this study, two concentrations of polyurethane solution, 10 and 15 wt % are used for electrospinning. Many studies have reported that electrospun fibers with lower concentration of polymer solution have smaller diameters . PU1 is the only sample electrospun from 10 wt % polyurethane solution and it has smaller average diameter than all the samples, except for PU5.…”
Section: Resultsmentioning
confidence: 91%
“…Most electrospun fibers are straight and only small traces of coiled fibers can be found in some studies . It is unique to have all coiled fibers in PU4 and high portion of coiled fibers in PU2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations